Preliminary Estimation of Engineering Bedrock Depths from Microtremor Array Measurements in Solo, Central Java, Indonesia - Sorja Koesuma; Mohamad Ridwan; Andri Dian Nugraha; Sri Widiyantoro; Yoichi Fukuda (Institute for Research and Community Services (LPPM) ITB, 2017)
In the last decade the city of Solo, located in Central Java, Indonesia, has grown significantly and become a major city. Many industries and hotels have been built in the city and its surroundings. This study aimed to determine the engineering bedrock depths in Solo, an important parameter in seismic hazard analysis. The microtremor array method was used to obtain 1D S-wave velocity profiles and construct layer depth maps. The spatial autocorrelation (SPAC) method was used to calculate the dispersion curves, while the S-wave velocity structure was derived using a genetic algorithm (GA). The results of the S-wave velocity structure in Solo show that there are four stratigraphic layers, where the engineering bedrock depths in Solo exist within the range from 145 to 185 m. The shape of the bedrock basin is elongated in an east-west direction.